Supervised consumption site enables cost savings by avoiding emergency services: a cost analysis study - Shahreen Khair; Cathy A. Eastwood; Mingshan Lu; Jennifer Jackson (Harm Reduction Journal, 2022)
Abstract Background and aims We report on a cost analysis study, using population level data to determine the emergency service costs avoided from emergency overdose management at supervised consumption services (SCS). Design We completed a cost analysis from a payer’s perspective. In this setting, there is a single-payer model of service delivery. Setting In Calgary, Canada, ‘Safeworks Harm Reduction Program’ was established in late 2017 and offers 24/7 access to SCS. The facility is a nurse-led service, available for client drop-in. We conducted a cost analysis for the entire duration of the program from November 2017 to January 2020, a period of 2 years and 3 months. Methods We assessed costs using the following factors from government health databases: monthly operational costs of providing services for drug consumption, cost of providing ambulance pre-hospital care for clients with overdoses who could not be revived at the facility, cost of initial treatment in an emergency department, and benefit of costs averted from overdoses that were successfully managed at the SCS. Results The proportion of clients who have overdosed at the SCS has decreased steadily for the duration of the program. The number of overdoses that can be managed on site at the SCS has trended upward, currently 98%. Each overdose that is managed at the SCS produces approximately $1600 CAD in cost savings, with a savings of over $2.3 million for the lifetime of the program. Conclusion Overdose management at an SCS creates cost savings by offsetting costs required for managing overdoses using emergency department and pre-hospital ambulance services.